Understanding American legislatures : the need for interpretive-qualitative research - Curry, James M. (Routledge, 2025)
"In this passionately argued book, James M. Curry introduces legislative scholars to the value and importance of interpretive research. His field guide for getting started on using an interpretive approach is designed so that the reader can understand a new methodological approach, not just new methods "tools" within a singular approach. Weaving in his own story from student to scholar, Curry begins by demystifying the importance and value of interpretive research. He later provides background on what interpretive methodologies are and how they differ from the quantitative and positivist approaches that dominate in the field. Focusing primarily on the study of the U.S. Congress and the 50 American state legislatures, Curry employs Richard Fenno's "soaking and poking" language as a bridge to the language of interpretivism, aiming to show legislative researchers how they can connect between the two and begin to use the richer terms of the latter in place of the former. Understanding American Legislatures is a must-read contribution to the study of legislatures and our discourse about methods in American politics"-- Provided by publisher.
Keywords: United States. -- Congress; Legislative bodies -- United States -- States.; Interpretive interactionism.; Research -- Methodology.; elektronické knihy; electronic books